ANALISA PENGARUH PROSES MANAJEMEN PENGETAHUAN TERHADAP KINERJA KARYAWAN PT MITRA KERINCI - Ondi Ondi; Hendra Lukito (Departemen Manajemen, 2020)
This study aims to find out and analyze the influence of the knowledge management process seen from knowledge acquisition, knowledge conversion, knowledge application, and knowledge protection on the performance of PT. Mitra Kerinci. This research is a causative study with quantitative methods. This study uses a non-probability sampling technique with a purposive sampling method, the criteria used are permanent employees (Permanent / PKWTT) with a working period of more than 5 years. The results of the study show that the knowledge management process seen from knowledge acquisition, knowledge conversion, and knowledge application has a positive and significant effect on employee performance while knowledge protection has a positive and not significant effect on the performance of employees of PT. Mitra Kerinci.